Virtual Laboratory Implementation in Molecular Biotechnology: Change in Prospective Biology Teachers’ Self-System and Mental Procedures - Idris, Tengku; Rahmat, Adi; Hidayat, Topik; Riandi, Riandi; Çakir, Mustafa (Jurnal Pendidikan IPA Indonesia, 2026)
Limitations in laboratory facilities and the demands of 21st-century learning require technology-based instructional innovations in molecular biotechnology courses. Therefore, the use of virtual laboratories has become a relevant solution for improving students’ procedural skills and fostering the development of their self-system in a sustainable manner. The objective of this study is to observe the influence of and improvements in students’ self-system and mental procedures during molecular biotechnology lectures using a virtual lab, as well as the relationship between these two variables. This study used two methods: an experimental single-group pretest-posttest design and a diary study. The research sample was selected purposively from two universities. The instruments used in this study were questionnaires, questions, and observation sheets. The research data were analyzed descriptively, using the Wilcoxon Signed-Rank test to test for differences in means, the Spearman’s rho correlation test, and linear regression testing. The results showed a moderate increase in the self-system category (N-gain = 0.59) from 67.60 to 87.58 and in the mental procedural category (N-gain = 0.69) from 15.42 to 68.94. Both increases were significant, with p-values (0.000) > α (0.05) and an effect size of 0.87 in the large category. Both variables showed a significant relationship (ρ = 0.40) and a self-system contribution to 11.5% increase in mental procedures. The findings of this study indicate that the use of virtual labs in biotechnology lectures can significantly improve students’ self-system and mental procedural abilities.